2006
DOI: 10.1093/europace/eul075
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular stimulation to prevent cardiac desynchronization: rationale, design, and endpoints of the ‘Biventricular Pacing for Atrioventricular Block to Prevent Cardiac Desynchronization (BioPace)’ study

Abstract: Despite the deleterious effects of cardiac dyssynchrony and the positive effects of cardiac resynchronization therapy, patients with high-degree atrioventricular block continue to receive desynchronizing right ventricular (RV) pacing systems. Although it is unclear whether the negative effects of RV pacing and left bundle branch block (LBBB) are comparable, and whether they depend on the presence and the degree of structural heart disease, one may hypothesize that RV pacing may have similar effects to LBBB. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(52 citation statements)
references
References 34 publications
0
52
0
Order By: Relevance
“…7,8,11,12 The inclusion of outpatient encounters in assessing the adverse impact of chronic RV pacing is particularly relevant given estimates that physician visits for HF account for ≈2% of all outpatient office visits and cost the healthcare system >$2 billion per year in the United States, representing an important opportunity for curbing healthcare expenditures. 27 Although it has been suggested that all patients undergoing pacemaker implantation with a predicted high burden of RV pacing should be implanted with a biventricular device, 7 the results of the PREVENT-HF study 28 and the preliminary results of the BioPace study 25,29 suggest that such a broad approach to biventricular pacing may not be justified. In general, patients with PICM seem to benefit from upgrade to biventricular pacing.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,11,12 The inclusion of outpatient encounters in assessing the adverse impact of chronic RV pacing is particularly relevant given estimates that physician visits for HF account for ≈2% of all outpatient office visits and cost the healthcare system >$2 billion per year in the United States, representing an important opportunity for curbing healthcare expenditures. 27 Although it has been suggested that all patients undergoing pacemaker implantation with a predicted high burden of RV pacing should be implanted with a biventricular device, 7 the results of the PREVENT-HF study 28 and the preliminary results of the BioPace study 25,29 suggest that such a broad approach to biventricular pacing may not be justified. In general, patients with PICM seem to benefit from upgrade to biventricular pacing.…”
Section: Discussionmentioning
confidence: 99%
“…36 The main criticism of this trial was small sample size (n=108 with ventricular pacing percentages ≥80%) and high crossover rate from biventricular to RV pacing. 42 The preliminary results of the larger (n=1,810) Biventricular pacing for Atrioventricular Block to prevent Cardiac Desynchronization (BIopACE) study 43 were released at the annual meeting of the European Society of Cardiology in 2014. The composite end point of death or first HF hospitalization was similar between biventricular and RV pacing …”
Section: Evidence Of Biventricular Pacing For Advanced Avb Patients Wmentioning
confidence: 99%
“…[40] One large randomised study looking at the effects on morbidity and mortality of CRT versus RV pacemaker systems in patients with a bradycardia has completed recruitment. [41] Although there is growing enthusiasm for right ventricular septal pacing there are as yet no hard endpoint data to support widespread adoption of this strategy. [42][36]…”
Section: Management Of Rv-pacing Associated LV Dysfunctionmentioning
confidence: 99%